Modeling longitudinal changes in 5m sprinting performance among young male tennis players - Kramer, T.; Valente-dos-Santos, J.; Coelho e Silva, M. J.; Malina, R. M.; Huijgen, B. C. H.; Smith, J.; Elferink-Gemser, M. T.; Visscher, C. (Perceptual and Motor Skills, 2016)
Year-to-year changes in sprinting in youth tennis players were examined in a mixed-longitudinal study (256 male players, aged 10-15 years: 993 measurements). Height (h), body mass (BM), lower limb explosive strength (LLES), and a 5-m sprint were measured over five years. During that period, players were classified as elite or sub-elite. To account for the repeated measurements within the individual nature of longitudinal data, multilevel random effects regression analyses were used. Sprint performance improved with age at each additional 1 year of age, thus predicting ~.016 sec improvement in five-meter sprint time by all variables of the model. It was possible to predict the performance of elite tennis players in the 5-m sprint (sec) for elite players (1.1493 - (0.0159 -- centered age) - (0.009 -- BM) - (0.044 -- LLES) and sub-elite players (1.1493 - (0.0159 -- centered age) + 0.0135 - (0.009 -- BM) -(0.044 -- LLES) - (0.0557 -- centered age). Sprint performance differences between elite and sub-elite players was related to longitudinal changes in body size and lower limb strength up until age 13. ABSTRACT FROM AUTHOR